Asymmetric Michael reaction of arylacetyl phosphonates to nitroalkenes with bifunctional amine-thiourea catalyst bearing multiple-hydrogen-bond donor: efficient construction of chiral α-substituted carboxylic ester compounds. Issue 21 (26th May 2016) - Zhang, Ming-Liang; Chen, Lin; You, Yong; Wang, Zhen-Hua; Yue, Deng-Feng; Zhang, Xiao-Mei; Xu, Xiao-Ying; Yuan, Wei-Cheng
Abstract: Catalytic asymmetric Michael addition of arylacetyl phosphonates to nitroalkenes was achieved with a chiral bifunctional amine-thiourea bearing a multiple-hydrogen-bond donor as a catalyst. A range of α-substituted carboxylic ester compounds with contiguous tertiary stereocenters could be smoothly obtained in good yields (up to 85%) and with high to excellent diastereo- and enantioselectivities (up to >99:1 dr and 95% ee). The large scale experiment and facile synthesis of a chiral γ-butyrolactam have also been demonstrated. Graphical abstract: